Post Covid Era: Future of Economies and World Order An Interdisciplinary Approach - Baykal, Mehmet; Haddock, Jorge; Dayanir, Aziz (Istanbul University Press, 2023)
EditörMehmet Baykal, Jorge Haddock, Aziz Dayanır Epidemics have always profoundly affected people's lives and caused radical changes. Many of the outbreaks in the past left deep traces on the societies of that period. For example, the Black Death is one of the most important, which started in 1346 and continued for years. The Black Death epidemic has killed millions and left a political and economic mark. According to Andrew Nikiforuk, the Black Death epidemic ended feudalism and led to the emergence of capitalism. In today's epidemic, Covid-19 has significant effects on health, both economic and political orders in our world. The virus, which first appeared in Wuhan, China's Hubei province, in the last months of 2019, spread to all countries around the world with an incredible speed in a few months, infecting more than six hundred million people and causing 6.5 million people to die. Thus, while the political and economic globalization processes have made positive contributions due to the market integration and human mobility that has accelerated in recent years, it has paved the way for public health risks. While the shock caused by the first wave in China and European countries is tried to be overcome, and normalization processes are tried to be advanced, health risks remain serious in the USA, Mexico, Brazil, and Russia countries where the epidemic caused the most loss of life. While country managers try to normalize gradually, vaccine development and vaccination studies continue at full speed. Vaccination cards have become the most crucial document and passports in world mobility. Now, all countries have learned to live with the pandemic. Still, to realistically evaluate the long-term effects of the Covid-19 epidemic on the world system and the global economy, it is necessary to reach a particular stage of the normalization process and to carry out comprehensive damage-detection studies on the reflections of the epidemic in areas such as growth, employment, and investment. The primary purpose of this book is to bring together various valuable studies that reveal the impact of the Covid-19 epidemic on the world economy and new world orders. This book has touched upon the subject in many fields, from tourism to the general economy, from new working systems to international relations. The studies in this book, do not cover all the changes that the Covid-19 pandemic has brought into our lives. But it reveals many approaches that will enable us to understand the pandemic's effects better.